Institusi Dakwah dan Persekitarannya dalam Membentuk Strategi Dakwah yang Berkesan - Ab. Ghani, Ab. Mumin (Jurnal Usuluddin, 1996)
Any organization including organization of Dakwah considered as an open system. By open system, we mean simply that the organization has transactions with other units in its task environment and is also affected by events in the general environment. The characteristics of the general environment constrain the activities of organization. The organization is also confronted by a task or specific environment. The task environment is composed of the organizations and individuals with which an organization is in direct interaction. The article tries to analyse organization of Dakwah and its environment in order to understand the characteristic of the both environment.